2006
DOI: 10.1007/s00464-005-0372-6
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and tissue blood flow responses to long-term pneumoperitoneum and hypercapnia in the pig

Abstract: The effect of CO2 on peritoneal blood flow during laparoscopic surgery is a local effect, and not attributable to central hemodynamic effects of CO2 pneumoperitoneum or high systemic levels of CO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The measurements of the liver blood flow and the results of the histological findings, which revealed dilatation of the sinusoid and central vein (containing red blood cells) and a focal lytic change, may indicate liver congestion. It has been reported that CO 2 pneumoperitoneum affects cardiac functions and results in increased pressure in the superior and inferior caval veins in a porcine pneumoperitoneum model (intra-abdominal pressure = 10 mm Hg) [27]. From the findings of the present experiments and the results of previous studies, we speculated that CO 2 pneumoperitoneum causes liver congestion through right ventricular cardiac overload and a decrease in the blood flow of the hepatic artery and portal vein; this results in an increased ICG retention rate and histological changes.…”
Section: Histological Findings In the Livermentioning
confidence: 99%
“…The measurements of the liver blood flow and the results of the histological findings, which revealed dilatation of the sinusoid and central vein (containing red blood cells) and a focal lytic change, may indicate liver congestion. It has been reported that CO 2 pneumoperitoneum affects cardiac functions and results in increased pressure in the superior and inferior caval veins in a porcine pneumoperitoneum model (intra-abdominal pressure = 10 mm Hg) [27]. From the findings of the present experiments and the results of previous studies, we speculated that CO 2 pneumoperitoneum causes liver congestion through right ventricular cardiac overload and a decrease in the blood flow of the hepatic artery and portal vein; this results in an increased ICG retention rate and histological changes.…”
Section: Histological Findings In the Livermentioning
confidence: 99%
“…However, in these two studies, the number of total cases was only 33 or 60, such a small sample size may be the key to the low incidence of hyperamylasemia. CO 2 pneumoperitoneum during laparoscopic surgery may have a significant effect on organs, especially intra-abdominal organ function, which may be the main influencing factor of hyperamylasemia in laparoscopic surgery (8)(9)(10)(11)(12)(13). The results of this study show that longer duration of pneumoperitoneum can significantly increase the incidence of postoperative hyperamylasemia.…”
Section: Discussionmentioning
confidence: 62%
“…been a better choice for patients who suffering colorectal cancer. A large number of studies have found that laparoscopic surgery can make damage to patients' lung (8), heart (9), kidney (10) and liver (11), also result in hypercapnia (12) and immunosuppression (13), while no studies of pancreas have been reported. Hyperamylasemia, referring to abnormal rise of serum amylase, is mostly considered as a manifestation of pancreatic tissue damage.…”
mentioning
confidence: 99%